KELAYAKAN DAN NILAI TAMBAH INDUSTRI RUMAH TANGGA KETELA POHON DI KECAMATAN PONJONG KABUPATEN GUNUNGKIDUL - , NURINA SOFIANA; , Dr. Ir. Any Suryantini, MM. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to determine the business feasibility, added value, and the factors that affect the added value of each cassava home industries in Bedoyo and Sumbergiri village, Ponjong district, Gunungkidul regency, Yogyakarta Province. There are two kinds of cassava home industries, they are krecek and lempeng. The feasibilty of cassava agroindsutry is calculated with R/C ratio, ï°/C ratio, breakeven point, and sensitivity analysis. The value-added data are calculated by using Hayamiâs method of value-added analysis. The added value data and its factors are tested by normality and classical assumptions test (autocorrelation, multicoliniearity, heteroskedasticity). The factors that influence the additional value of cassava home industries are analyzed by multiple linear regression in OLS method. The result of data analysis showed that : 1) Krecek and lempeng home industries that is based on R/C ratio value, ï°/C ratio value, break event point analysis and senstivity analysis are feasible. 2) Added value of proccessed raw krecek by Rp 2.067,38/kginput, fried krecek Rp. 2.749,51/kginput,and lempeng Rp. 16.823,83/ kginput.3) Multiple linear regression analysis on factors that determine the additional value showed the factors that significally influence the amount of added value are the product price and total raw materials. Therefore, this research concludes that cassava home industries in Ponjong District Gunungkidul regency are beneficial and feasible to develop. Keywords : Cassava, Feasibility, Home Industry, Value-added